Periodontal Conditions of Abutments and Non-Abutments in Removable Partial Dentures over 7 Years of Use - Porto Carreiro, Adriana da Fonte; Dias, Kassia de Carvalho [UNESP]; Correia Lopes, Ana Lilian; Bastos Machado Resende, Camila Maria; Luz de Aquino Martins, Ana Rafaela (Wiley-Blackwell, 2017)
PurposeTo evaluate the periodontal conditions and integrity of abutment and non-abutment teeth of patients evaluated 7 years after insertion of the removable partial denture (RPD). Materials and MethodsTwenty-two patients (17 women, 5 men) were assessed at the moment of denture insertion and 7 years later. The following items were verified in each assessment: bleeding on probing (BP), probing depth (PD), gingival recession (GR), and mobility (M), comparing direct and indirect abutment teeth, and the teeth not involved in the denture design. Tooth integrity was also evaluated and classified as intact when no caries or fractures were observed. The Kruskal-Wallis test was used to reveal statistical significance between the groups (p = 0.05) as well as the Bonferrroni-corrected Mann-Whitney test for post hoc comparison. The Wilcoxon test was used for evaluation within the group over time. Fisher's exact test was applied to cross data about abutment integrity. ResultsStatistically significant differences were found for GR (baseline, p < 0.001; 7 years, p < 0.001) and PD (baseline, p = 0.001; 7 years = 0.004) between the three groups at baseline and after 7 years of follow-up. Mean BP and M values increased from initial assessment to after 7 years of RPD use in every group, but no statistically significant difference was found between the groups. For abutment integrity, a statistically significant difference (p = 0.028) was observed, and the direct abutment exhibited more (33.3%) caries and fractures. ConclusionRPDs generated more periodontal damage to direct abutments, since higher gingival recession probing depth indexes, and presence of caries and fractures were observed in comparison to indirect abutments and non-abutments.
Keywords: Oral hygiene; periodontal diseases; removable partial denture; longitudinal studies; abutment teeth; tooth loss